How Do Organizational Visibility, Regulation, And Energy Use Shape The Future Of Green Finance? A Systematic Review - Erdapuspita, Zsa Zsa Ilmanabilah; Sukmadilaga, Citra; Tanzil, Nanny Dewi (Universitas Muhammadiyah Pontianak, 2025)
The aim of this study is to review publications on green finance between 2020 and 2025 using a systematic literature review (SLRs). Using the PRISMA protocol, 66 relevant articles were sourced from the Scopus database, identified through keywords including